On the trade-off performance curve of vibration isolation controlled by passive or adaptive dampings - Viet, La Duc (Vietnam Journal of Mechanics, 2023)
This paper addresses an on-off adaptive damping isolation, in which the damping can be frequency dependent. The comparison with the passive isolation is illustrated by the trade off performance curve, which is shown the relation between the displacement and force transmissibility. The adaptive control is based on on-off dampings and a switching frequency. The analytical optimization of the adaptive damping law can be obtained. The optimized adaptive damping control showed a remarkable improvement comparing with the passive one. At last, a self-made magnetorheological fluid is introduced to show the capability to provide the variable damping.